ANALISIS KESESUAIAN GERAK TENDANGAN SABIT PADA ATLIT PENCAK SILAT PERGURUAN PERISAI DIRI KECAMATAN WEDUNG - Bakhtiar, Ananda; Irawan, Fajar Awang (Journal of Sport and Exercise Science, 2023)
This study aims to determine the development of the athlete's sickle kick in accordance with the mechanical studies needed so that improvements can be made and competitors can perform the sickle kick more realistically and limit injuries. The reason for this research is to examine the biomechanics, and the suitability of the sickle kick movement in martial arts athletes at the Perisai Diri College, Wedung District. The total population in this study were 10 participants in a fighting technique competition from Perisai Diri, Wedung District. This study uses a purposive sample method. The development of the martial arts sickle kick from the tide position stage, take-off stage to the effect stage is the focal point of the article in this review. The retrieval technique used in this research is quantitative explanation. The procedure for collecting information uses documentation techniques. The results of this study indicate that based on a biomechanical analysis of the suitability of the motion of the sickle kick, it is included in the "appropriate" criteria. Based on the results of the biomechanical analysis of the sickle kick and the timing of the sickle kick, this movement is effectively used to carry out attack movements in a martial arts match. The conclusion of this study is that there is a need for improvements in the motion of the sickle kick in the martial arts athlete Perisai Diri, Wedung District based on biomechanics, so that the kick movement can be included in the "very appropriate" category. An increase in the movement speed of the sickle kick is needed to be included in the "very good" category. In addition, increasing the correctness of motion and kick speed is expected to increase the level of suitability of the sickle kick in carrying out attacks during the match.